Lepidoptera abundance and diversity as a quantitative measure of ecosystem function in bioretention design - Raleigh D. Myers; Bridget Wadzuk; Samantha K. Chapman (Ecological Indicators, 2025)
The choices of engineers and other professionals working in urban environments can either mitigate or exacerbate drivers of ecosystem and biodiversity decline. To date, engineers designing bioretention basins for management of urban surface runoff typically have not considered implications of their design and management decisions on terrestrial ecosystem structure and function. However, a foundation of knowledge sufficient to evaluate design decisions in light of ecosystem functions exists in the fields of engineering and ecology, and this knowledge can be connected to improve design outcomes. Bioretention system functions considered in this paper are hydrologic regulation, production, nutrient retention, and habitat provisioning. We 1) review existing knowledge on the use of quantitative criteria to advance terrestrial ecosystem objectives in bioretention design, with a focus on Lepidoptera abundance and diversity as a proxy for these ecosystem functions, 2) report results of a literature review identifying gaps in knowledge and interdisciplinary communication limiting achievement of terrestrial ecosystem objectives, and 3) connect existing data and literature across disciplines to propose a novel design and plant choice approach to fill these gaps. A key criterion recommended as a proxy for terrestrial ecosystem function in bioretention basins is the number of Lepidoptera species supported in the larval stage by the plant genera selected by the designer. Designers can adjust plant choice to maximize this value, subject to tradeoffs with other design objectives and site-specific constraints. We conclude by presenting a set of questions to guide future research and providing recommendations for translating research findings into professional practice.